2021
DOI: 10.3390/su132011480
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Dining-Out Trends Using Big Data: Focusing on Changes since COVID-19

Abstract: This study examined consumers’ emotions and needs related to dining-out experiences before and during the COVID-19 crisis. This study identifies words closely associated with the keyword “dining-out” based on big data gleaned from social media and investigates consumers’ perceptions of dining-out and related issues before and after COVID-19. The research findings can be summarized as follows: In 2019, frequently appearing dining-related words were dining-out, family, famous restaurant, recommend, and dinner. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
(34 reference statements)
6
11
0
Order By: Relevance
“…(2014) also found that GPQ impacted consumers' positive emotions. As in the present study, Jung et al. (2021) also found that increasing GPQ reduces consumers' negative emotions.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…(2014) also found that GPQ impacted consumers' positive emotions. As in the present study, Jung et al. (2021) also found that increasing GPQ reduces consumers' negative emotions.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 89%
“…Shahzadi et al (2018) and Marinkovic et al (2014) also found that GPQ impacted consumers' positive emotions. As in the present study, Jung et al (2021) also found that increasing GPQ reduces consumers' negative emotions. The GPQ, associated with positive emotions ( § 5 0.431) and negative emotions ( § 5 0.07), helped explain consumer memorable experiences (R 2 5 35.6%).…”
Section: Nomological Model Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Big Data applications assisted in strengthening the resistance to the global financial crisis's consequence [95]. Big Data applications play an important role in handling such pandemic situations as predicting COVID-19 outbreaks and diagnosing COVID-19 cases and spreading patterns, as described below [76].…”
Section: Rq1: Role Of Big Data Applications For Fighting the Covid-19...mentioning
confidence: 99%
“…Through the quantification of social media data, they found a method that can evaluate a service quality of the restaurant. Jung et al [ 36 ] studied the changes in satisfaction with dining out before and after the pandemic through the content of comments on social media data and concluded that the study of changes in consumer dining needs is an important way to help restaurant companies adapt to the development of social changes and promote sustainable management. Koufie et al [ 37 ] discuss what millennials look for in restaurant reviews and the importance of a restaurant’s online word-of-mouth among today’s millennial population, and also emphasize that social media should be incorporated into the restaurant’s marketing communication strategy in restaurant management.…”
Section: Introductionmentioning
confidence: 99%